SOME ASPECTS EMPLOYMENT LAW OF UZBEKISTAN (World Bulletin of Management and Law, 2022)
The current study aims to express some aspects of Uzbek employment law particularly, employment contracts, fixed-term/open-ended contracts, trial period, notice period, holidays and annual leave, maternity leave, sickness and disability leave, salary
Keywords: Employment contracts; fixed-term/open-ended contracts; trial period; notice period